Pengembangan Media Pembelajaran Monopoli pada Materi Fungsi Bagian Tubuh Hewan dan Tumbuhan di Kelas Bagi Siswa Kelas 4 SD - Wulan Suci Rimadhani; Karimatus Saidah; Muhamad Basori (Departement of Mathematics Education, 2023)
The problems of this research are 1) What is the validity of Monopoly learning media on the function material of animal and plant body parts for fourth grade students of Sanggrahan 2 Prambon Nganjuk Elementary School 2) What is the practicality of Monopoly learning media on material function of animal and plant body parts for fourth grade students of Sanggrahan 2 Prambon Nganjuk Elementary School 3) How is the effectiveness of Monopoly learning media on material function of animal and plant body parts for Grade IV students at SDN Sanggrahan 2 Prambon Nganjuk This research is a type of development research with reference to research and development. According to Robert Maribe Branch (2009) in Sugiyono (2015: 38)